Közigazgatás: tegnap, ma, holnap - Lőrincz, Lajos (Tér és Társadalom, 1999)
Administration – where built up – is unchanged from ancient times until recently, and it is expected not to be changed in the future even. Differences are only emerged from the different approaches of works about administration and the judgement of communal and individual values. Real processes prove that strong administration develops where public interest has a high priority – either for prime necessities, or for other reasons (Egypt, Chine, the states of enlightened absolutism). Administration hasn’t been established (the states of early feudalism) or has devel- oped abort (the city-states of ancient Greece, America in the 17-19 centuries) in societies, individual values were favoured in which. The world has became uniform for today: the administration, i.e. the role of governing in favour of public interest is increasing without stopping in real life, despite of every opposite literary, political, intellectual and entrepreneurial community of interests, request, demand, deliberate action supported by international criminal gangs. It’s because of the world globalisation and the increasing complexity of social problems. In this respect Hungary follows the general trend of development. So it wouldn’t be right to value it differently with regard to the turbulence of groupings with egoistic interests presented previously.